Protein kinase C-α is upregulated by IMP1 in melanoma and is linked to poor survival. Issue 5 (October 2019) - Mahapatra, Lily; Andruska, Neal; Mao, Chengjian; Gruber, Stephen B.; Johnson, Timothy M.; Fullen, Douglass R.; Raskin, Leon; Shapiro, David J.
Abstract : The oncofetal mRNA-binding protein, IMP1 or insulin-like growth factor-2 mRNA-binding protein 1 (IGF2BP1), promotes the overexpression of several oncogenic proteins by binding to and stabilizing their mRNAs. IMP1 is frequently overexpressed in melanoma and is associated with a poor prognosis, but the full spectrum of IMP1 target transcripts remains unknown. Here, we report the identification of protein kinase C-α (PKCα), as a novel molecular target of IMP1. Overexpression of IMP1 resulted in increased levels of PKCα, while RNAi knockdown of IMP1 resulted in decreased PKCα mRNA stability, PKCα protein levels, and MAPK/ERK activation. In addition to IMP1 acting as a positive regulator of PKCα mRNA, we also report the identification of miR-340 as a negative regulator of PKCα mRNA. In melanoma cancer cells, inhibition of miR-340 led to increased PKCα protein levels. PKCα plays important roles in numerous signaling pathways including the MAPK/ERK signaling pathway. PKCα activates RAF1, which in turn activates MEK1, and activates downstream transcriptional targets of MAPK through activation of JNK signaling. Together, these pathways provide a way to activate MAPK signaling downstream of BRAF and MEK1 inhibitors, which are commonly used to treat melanoma. Analysis of 117 melanoma tumors samples showed that overexpression of PKCα is associated with poorer overall survival. In patients harboring BRAF V600E or NRAS mutations, PKCα overexpression is associated with an 11-fold increased risk of death. Thus, PKCα mRNA is a novel target of IMP1, which is commonly overexpressed in melanoma and is linked to poorer overall survival.